Factors affecting regeneration from root fragments in two Physalis species - Abdullahi, A.E.; Cavers, P.B. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 1997)
Smooth ground-cherry (Physalis virginiana var. subglabrata) and clammy ground-cherry (P. heterophylla) are native weeds that are becoming more common in arable land in southern Ontario. Much of their success stems from vegetative propagation, especially after dispersal of root fragments during cultivation. Root fragments of different lengths, collected at different life cycle stages, from different parts of the root System and replanted at different depths and orientations in the soil, were tested for regeneration in the field and the greenhouse. No fragments left on the soil surface regenerated. Shallow (5 cm) burial led to the fastest regeneration. Fragments as short as 2.5 cm regenerated but the highest percentage regeneration was from fragments 10- cm long. Orientation had no effect on the capacity of root fragments to regenerate nor on the time taken to regenerate in either species. In both species, fewer root fragments sampled from plants at the fruit dispersal stage regenerated in the same season than fragments obtained at the early vegetative stage. Root fragments obtained from parts of the root System closest to the crown had the least regeneration. Root fragments with preformed visible buds at planting time regenerated faster than those with no preformed buds. In both the greenhouse and the field, smooth ground-cherry shoots emerged faster than those of clammy ground-cherry. These results suggest that reduction in ground-cherry infestations could be achieved by cultivating and dragging fragments to the surface.